2009
DOI: 10.1227/01.neu.0000341903.11527.2f
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Fever and Outcome in Surgical Patients With Aneurysmal Subarachnoid Hemorrhage

Abstract: These findings suggest that fever is associated with worsened outcome in surgical subarachnoid hemorrhage patients, although, because the association between fever and the primary outcome measure for the trial is dependent on the covariates used in the analysis (particularly operative events and delayed ischemic neurological deficits), we cannot rule out the possibility that fever is a marker for other events. Only a formal trial of fever treatment or prevention can address this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…The study showed that hypothermia was relatively safe but was not associated with a beneficial effect in mortality or neurological outcome among patients with good-grade aSAH. 189 In addition, intraoperative hypothermia had no beneficial effect on neuropsychological function after SAH. 190 Of note, the power of these 2 studies was not sufficient to detect more modest benefits from hypothermia, and there were some trends in favor of hypothermia for secondary end points.…”
Section: Anesthetic Management During Surgical and Endovascular Treatmentioning
confidence: 97%
“…The study showed that hypothermia was relatively safe but was not associated with a beneficial effect in mortality or neurological outcome among patients with good-grade aSAH. 189 In addition, intraoperative hypothermia had no beneficial effect on neuropsychological function after SAH. 190 Of note, the power of these 2 studies was not sufficient to detect more modest benefits from hypothermia, and there were some trends in favor of hypothermia for secondary end points.…”
Section: Anesthetic Management During Surgical and Endovascular Treatmentioning
confidence: 97%
“…However, one can only definitively say that fever is associated with worsened outcomes, it may not be causative. In other words, it may simply be a marker of bad outcomes (45).…”
Section: Therapeutic Hypothermia For Subarachnoid Hemorrhagementioning
confidence: 99%
“…Often, an infectious source is not found. Greater burden of fever is related to worse outcomes after IPH (51) and SAH (52,53).…”
Section: Treatment and Medical Complications Of Intracranial Hemorrhamentioning
confidence: 99%